2009
DOI: 10.1007/s10545-009-1238-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, treatment, follow‐up and gene mutation analysis in four Chinese children with biotinidase deficiency

Abstract: Early recognition of biotinidase deficiency is crucial to avoid permanent damage. Determination of biotinidase activity should be included in neonatal screening in China. Exon 4 may be a hot-spot for biotinidase gene mutations in Chinese patients. Four novel gene variations may be disease-causing mutations and should be confirmed by expression studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…The commonest neurological, cutaneous and biochemical manifestations were: seizure (9/10); alopecia (9/10); organic aciduria (4/6). This observation has been seen previously in various ethnic populations and in case reports from India [8][9][10][11][12]. Iranian case series found that seizures (13/16), alopecia (8/16), abnormal auditory brainstem response (4/16), abnormal lactate and ammonia (8/16) were the common manifestations [13].…”
Section: Discussionsupporting
confidence: 78%
“…The commonest neurological, cutaneous and biochemical manifestations were: seizure (9/10); alopecia (9/10); organic aciduria (4/6). This observation has been seen previously in various ethnic populations and in case reports from India [8][9][10][11][12]. Iranian case series found that seizures (13/16), alopecia (8/16), abnormal auditory brainstem response (4/16), abnormal lactate and ammonia (8/16) were the common manifestations [13].…”
Section: Discussionsupporting
confidence: 78%
“…Some groups have analysed the initial portion of the BTD gene in patients with BD [3134]. These studies observed a point variant in the promoter [32] and another in the 5’UTR [35].…”
Section: Discussionmentioning
confidence: 99%
“…The cost per QALY gained decreased only slightly when we assumed no treatment of partial BD cases. This finding, alongside the anecdotal evidence that some patients with partial BD do experience clinical symptoms if untreated, 22,30 and the lack of toxicity for biotin 1 build a stronger case for the treatment of detected partial BD.…”
Section: Discussionmentioning
confidence: 90%
“…7-10,13,22-24 Therefore, we assumed that BD cases detected The probabilities of exhibiting symptoms in cases not detected by NBS are based on meta-analyzing the evidence from identified case series studies. 6,8,22,[25][26][27][28][29][30] The probabilities of each outcome are presented in Table 1, including death, seizures, hypotonia, skin problems, cognitive deficits, optic atrophy, and hearing loss (see Supplemental Information for more details). The base case analysis assumes, conservatively, that only profound cases experience clinical complications, whereas in a separate analysis we allow for partial BD cases to also exhibit some of the features that have been documented in the literature among these patients (ie, seizures, skin problems, hearing loss, and cognitive deficits).…”
Section: Overviewmentioning
confidence: 99%